HBV and HIV/HBV Infected Patients Have Distinct Immune Exhaustion and Apoptotic Serum Biomarker Profiles - Mohamed Tarek M. Shata; Enass A. Abdel-hameed; Susan D. Rouster; Li Yu; Meina Liang; Esther Song; Mark T. Esser; Norah Shire; Kenneth E. Sherman (Case Western Reserve University, 2019)
Background: Hepatitis B virus (HBV) infection is a leading cause of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma worldwide. Due to their shared routes of transmission, approximately 10% of HIV-infected patients worldwide are chronically coinfected with HBV. Additionally, liver disease has become a major cause of morbidity and mortality in HBV/HIV coinfected patients due to prolonged survival with the success of antiretroviral therapy. The relationship between immune exhaustion markers (PD-1/PD-L1) and apoptotic markers such as Fas/FasL, TGFβ1, TNF-α, and Th1/Th2 cytokines are not clearly delineated in HBV/HIV coinfection. Methods: Levels of soluble Fas/FasL, TGFβ1, TNF-α, and sPD-1/sPD-L1 as well as Th1 and Th2 cytokines were evaluated in the sera of HBV-monoinfected (n=30) and HBV/HIV-coinfected (n=15) patients and compared to levels in healthy controls (n=20). Results: HBV-monoinfected patients had significantly lower levels of the anti-inflammatory cytokine IL-4 (P < 0.05) and higher levels of apoptotic markers sFas, sFasL, and TGFβ-1 (P < 0.001) compared to healthy controls. Coinfection with HIV was associated with higher levels of sFas, TNF-α, and sPD-L1 (P < 0.005), and higher levels of the pro-inflammatory cytokines IL-6, IL-8, and IL-12p70 (P < 0.05) compared to healthy controls. Patients with HBV infection had a unique biomarker clustering profile comprised of IFN-γ, IL12p70, IL-10, IL-6, and TNF-α that was distinct from the profile of the healthy controls, and the unique HIV/HBV profile comprised GM-CSF, IL-4, IL-2, IFN-γ, IL12p70, IL-7, IL-10, and IL-1β. In HBV monoinfection a significant correlation between sFasL and PD1(r = 0.46, P= < 0.05) and between sFas and PDL1 (r = 0.48, P= < 0.01) was observed. Conclusion: HBV-infected and HBV/HIV-coinfected patients have unique apoptosis and inflammatory biomarker profiles that distinguish them from each other and healthy controls. The utilization of those unique biomarker profiles for monitoring disease progression or identifying individuals who may benefit from novel immunotherapies such as anti-PD-L1 or anti-PD-1 checkpoint inhibitors appears promising and warrants further investigation.